The group guidance of discussion technique effect towards santri’s english communication skill - Hasyim, Umar Alfaruq A.; Arifin, M. Zainal; Saputra, Andika Ari; Qoni’ah, Umi; Maulana, M. Fikri; Sabri, Farhana (At- Ta'lim : Jurnal Pendidikan, 2025)
This research aims to determine the effect of group guidance using discussion techniques on santri’s ability to apply english communication skill. This research method uses experiments with 8 research subjects, which were obtained from the results of questionnaire analysis whose validity has been tested as a support for the guidance and counseling service approach. Data was analyzed descriptively qualitatively. The results of this experimental research show that group guidance using discussion techniques can influence santri’s ability to apply english communication skill on the 8 students who were the subjects. Score of students' ability to apply english communication skill before being given action (pre-test) namely 10.75 which is included in the low category. After taking action (post-test) the score is 15.87 which is included in the sufficient category. Thus, it can be recommended that group guidance using discussion techniques can influence students' ability to apply english communication skill.